Two petro-states diverge: explaining the institutional evolution of Nigeria and Angola - Harvey, Ross (School of Economics, 2020)
It is well-established that oil wealth in weakly institutionalised states tends to undermine development instead of catalysing it. Cross-country regressions, however, struggle to explain why comparably oil-wealthy countries such as Nigeria and Angola experience different political and economic outcomes over time. This thesis explains these differing outcomes through a theoretical lens derived from the New Institutional Economics and Political Settlements literature. Methodologically, it employs analytic narrative - the application of a game theoretic model to a historical puzzle to produce a thin explanation - and treats economic transactions as the key unit of analysis for understanding why particular outcomes obtain and not others. As a comparable site of analysis, I select the oil-for-infrastructure deals that were negotiated in Angola and Nigeria with Asian National Oil Companies between 2004 and 2007. Contrary to expectation, the deals were struck in Angola but failed in Nigeria. I hypothesise that the differential outcome reflects the varying quality of the institutional arrangements in each country for engaging foreign investors. This differential institutional quality resulted in differing commitment credibility over time, which partly accounts for deal failure in Nigeria. Divergent political economy trajectories and political settlements account for these differences. I use a game theory model that explains heterogeneity within authoritarian regimes to test these hypotheses. Application of the model to Angola and Nigeria respectively shows that Angolan dictator, José Eduardo dos Santos, was able to consolidate power within six years of becoming the head of state by successfully eliminating potential threats to his dictatorial ambitions. Under this closed, stable regime, foreign investors perceived greater levels of commitment credibility and struck deals. Nigeria’s uneven institutional evolution towards greater openness was punctuated by multiple successful coups and occasional civilian rule between long periods of military autocracy. The resultant instability undermined the perception of credibility, explaining why the deals failed. The thesis closes with a description of how Nigeria and Angola’s political economies have evolved since the oil-price crash of 2014, including how dos Santos unexpectedly lost power, and poses questions for future research.